Ductility enhancement of reinforced concrete beam using Engineered Cementitious Composites in the tension zone. (2020) - Siva, M.; Sasikumar, T.; Raj, P.S. Aravind; Divahar, R.
Abstract: In this study, the optimum flexural properties (viz., ductility and crack arresting mechanism) of Engineered Cementitious Composites (ECC) in the tension zone (1/3 of depth) along with conventional M25 grade concrete in the compression zone (2/3 of depth) of beam is investigated. Polyvinyl alcohol (PVA) fibres and Polypropylene (PP) fibres are used separately in two different ECC mixes. A comparative analysis on flexural strength, deflection, ductility and strain along the depth are carried out for control, PVA-ECC and PP-ECC composite beams. From the flexure studies, it is found that the ultimate load carrying capacity of PVA-ECC fibre composite beam is 16.7% more than control beam and 3.63% more than the PP-ECC fibre composite beam. Deflection of PVA-ECC fibre composite beam is found to be 40.3% and 12.5% less than control beam and PP fibre composite beam respectively, in addition, the stiffness of the PVA-ECC composite beams in the pre-cracking stage is observed to be slightly lesser compared to control and PP-ECC fibre composite beam. From the studies, it is clear that the use of ECC in the cover region, improved the flexural behaviour and ductility by avoiding brittle crack failure. The PVA-ECC fibre based composite beam performed relatively better than PP-ECC fibre based composite beam with respect to strength aspect.